Soil Nutrient Inflow-Outflow Dynamics and Balance on Agricultural Cultivated Farms in Northern Ethiopia - Esubalew, Tilahun; Amare, Tadele; Molla, Eyayu (International Journal on Food, Agriculture and Natural Resources, 2024)
Soil fertility is the controlling factor of  agricultural production worldwide including Waghimera zone, Ethiopia. However, it has been diminished from time to time and leads to low crop yield. Measuring of soil nutrient inflow-outflow affords necessary information about the current nutrient status of the soils, and to take appropriate nutrient management practices. The study was conducted to estimate the full soil nutrient balance of cultivated farms in the northern, of Ethiopia, in the 2020/21 main season. Inflow and Outflow of N, P, and K into, and out of farms were measured through the interview, field measurement, laboratory analysis, USLE model, and pedo-transfer functions. The full N balance of barley, tef, and wheat were -66.7, -8.9, and -47.1 kg ha-1 yr-1, respectively. P full balance was -5.4, 1.4, and -1.9 kg ha-1 yr-1 for barley, tef, and wheat farms, respectively. Whereas, K balance was also -12.4, -3.3, and -6 kg ha-1 yr-1 for barley, tef, a nd wheat, respectively. The balance quantification was done by subtracting nutrient outflows from the inflows. The results revealed that N, P, and K had negative balances except for P in tef. Grain yield and crop residue removal were the major paths of nutrient loss. To sustain, and boost agricultural production, reversing the imbalance between inflows, and outflows is critically essential for the study area. The current highly depleted nutrient should be corrected by adding sufficient organic, and inorganic nutrient sources, like in situ manuring, biochar, green manure, and remaining crop residue in the fields.